Delayed Endoluminal Vacuum Therapy for Rectal Anastomotic Leaks after Rectal Resection in a Swine Model: A New Treatment Option - Laura H. Rosenberger; Amber Shada; Lane A. Ritter; David M. Mauro; Mark J. Mentrikoski; Sanford H. Feldman; Daniel E. Kleiner (Wiley, 2014)
Abstract Anastomotic leaks are a dreaded surgical complication following colorectal operations. Creation of a temporary proximal diverting ileostomy is used in high‐risk anastomoses, however, additional surgical risk is accumulated with its creation and reversal. Endoluminal vacuum therapy has been shown to seal anastomotic defects in the prophylactic setting in a pig model and we hypothesized it could be utilized in a delayed fashion to rescue subjects with an active anastomotic leak. Yorkshire pigs underwent rectal resection, intentional leak confirmed by fluoroscopy, and endoluminal vacuum therapy device placement to low continuous suction. Following treatment, a contrast enema and necropsy was performed for gross and histopathology. Pigs underwent 2 (or 5) days of free intraperitoneal leak prior to device placement and 5 (or 7) subsequent days of endoluminal vacuum therapy. Six of seven early‐treated pigs sealed their anastomotic defect, while two of the four treated pigs in this extended group sealed the defect. Endoluminal vacuum therapy is feasible and well tolerated in a pig model, and it has been shown to seal a significant number of freely leaking anastomoses in the early period (86%). This technology warrants further study as it may provide a noninvasive means to treatment of anastomotic leaks.